HASIL BELAJAR DAN MINAT BERWIRAUSAHA KULINER SISWA SMK: A SYSTEMATIC LITERATURE REVIEW - Refi, FebrianaWulandari; Asmar Yulastri; Henny Yustisia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational education plays a crucial role in preparing students to enter the workforce and create jobs independently through entrepreneurial activities. This article examines the interaction between student learning outcomes and entrepreneurial interest in culinary education among vocational high school students. This article utilizes a systematic literature review of previous research to provide a clearer picture of the influence of learning outcomes on culinary entrepreneurial interest among vocational high school students. This literature review provides a comprehensive analysis of basic concepts, influencing factors, and practical strategies for improving academic achievement and entrepreneurship in vocational settings. The results of the literature review indicate that student learning outcomes have a positive effect on entrepreneurial interest. The findings of this literature review are projected to serve as a guide for educators in streamlining problem-based learning to improve students' numeracy and literacy skills.